2017
DOI: 10.1007/s11030-017-9727-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of arylpyrazoles as fungicides against phytopathogenic fungi

Abstract: 3-phenol-1H-pyrazoles (2), 4-halogeno-3-phenol-1H-pyrazoles (3) and 2-(1-phenol-1H-pyrazol-5-yl)phenols (4) were prepared by the condensation of (E)-3-(dimethylamino)-1-phenylprop-2-en-1-ones and hydrazine hydrate or phenylhydrazine in good yields. They were evaluated against five phytopathogens fungi, namely Cytospora sp., Colletotrichum gloeosporioides, Botrytis cinerea, Alternaria solani and Fusarium solani in vitro. Most of the above-mentioned compounds exhibited activities. For example, 4-chloro-2-(1H-pyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…3,4‐Disubstituted pyrazoles were reported to be valuable fungicides against phytopathogenic fungi [15] . Fezolamine [3,4‐diphenyl‐1H‐pyrazole‐1‐propanamines, 80410‐36‐2] is an antidepressant drug, which can be prepared by Michael addition of acrylonitrile to diphenylpyrazole followed by reductive alkylation of the resulting diphenylpyrazolepropionitriles [16] …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4‐Disubstituted pyrazoles were reported to be valuable fungicides against phytopathogenic fungi [15] . Fezolamine [3,4‐diphenyl‐1H‐pyrazole‐1‐propanamines, 80410‐36‐2] is an antidepressant drug, which can be prepared by Michael addition of acrylonitrile to diphenylpyrazole followed by reductive alkylation of the resulting diphenylpyrazolepropionitriles [16] …”
Section: Resultsmentioning
confidence: 99%
“…3,4-Disubstituted pyrazoles were reported to be valuable fungicides against phytopathogenic fungi. [15] Fezolamine [3,4diphenyl-1H-pyrazole-1-propanamines, 80410-36-2] is an antidepressant drug, which can be prepared by Michael addition of acrylonitrile to diphenylpyrazole followed by reductive alkylation of the resulting diphenylpyrazolepropionitriles. [16] After sequential one-pot synthesis of pyrazoles with substitutions at 1, 3, and 5 position, the synthesis of 3,4disubstituted pyrazoles were further explored.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most volatile compound produced by CZ-6 is 2-methylpropylhydrazine. Although no studies have shown that it antagonizes pathogens, its derivatives can be synthesized into pesticides, suggesting the strain's potential use as microbial pesticide [ 56 ]. Recent study has shown that the main VOC produced by the CZ-6 strain, 2-nonanone, can inhibit anthracnose fungus, Candida , and Staphylococcus [ 57 ]; 2-heptanone has also been reported to have strong antifungal activity.…”
Section: Discussionmentioning
confidence: 99%
“…Enaminones are a kind of important structures, which widely exist in numerous pharmaceuticals and agrochemicals [1] . Moreover, enaminones are often used as important versatile intermediates for the preparation of various heterocycles, [2] such as furans, [2a] pyridines, [2b–d] pyrazoles, [2e,f] thiazines, [2g] quinolones [2h,i] . The functionalization of enaminones is a promising strategy to obtain valuable compounds [3] .…”
Section: Methodsmentioning
confidence: 99%